Exploring the minescape: engaging with the complexity of the extractive sector. Issue 2 (14th December 2015) - Ey, Melina; Sherval, Meg
Abstract : This paper introduces the concept of the minescape as a conceptual and imaginative tool through which to integrate and represent growing shifts in the way natural resource extraction is understood. In recent years, traditional perceptions of extractive processes as 'natural' and purely economic in nature have been increasingly challenged by new developments within the fields of human geography and anthropology. Likewise, growing insights into the multifaceted socio‐cultural terrain of extractive operations, and burgeoning work on the interplay of materiality and discourse within the extractive sector, have also transformed the way that extractive processes (and their potentialities) are being conceptualised. The concept of the minescape aims to draw together significant insights concerning the extractive sector, which are increasingly being deployed when representing extractive spaces. Appropriating the term from its current use in fine art, the minescape joins a number of recent appropriations of the 'scapes' suffix to capture the expanding analytical scope of extractive sector inquiry. In essence, the minescape stands as a representational tool that underscores the intricate ways in which extractive processes are imbued with complex socio‐cultural dynamics, and powerful material and discursive elements.